Functional semi-finished fish product evaluation: organoleptic and evidence in vivo - Moldagaliyeva, Dinara; Uzakov, Yasin; Sarsembayeva, Nurzhan; Ibazhanova, Assem; Jussipbekova, Balzhan; Nurakhova, Alma; Artykbayeva, Ulbobek; Baimuratova, Mairash (Frontiers in Sustainable Food Systems, 2023)
The development of functional products is a new promising trend in the modern food industry. The research aims to study the developed functional semi-finished fish product – crude smoked sausage – to confirm its quality indicators, effectiveness, and safety for living organisms. Organoleptic and histological assessments of the product were performed. Also, a series of experiments were conducted to assess the product's safety and functional properties by feeding Enteracol with different concentrations of the active ingredient (Escherichia coli 64G strain) to white mice. The assessment properties of the proposed product (crude smoked sausage with a probiotic component) demonstrated its high consumer qualities. According to the controlled prospective study results, it was confirmed that the product was safe and non-toxic for living organisms. At the same time, the assessment of the product’s antagonistic activity revealed its high protective effect (85-100% survival rate of animals in the experimental groups). This article indicates that the developed product can be launched into production in view of its safety and non-toxicity for living organisms, its stimulating effect, and the antagonistic activity against pathogenic and opportunistic Enterobacteriaceae. However, the stimulating effect of the product requires a more thorough analysis in the long term.